2016
DOI: 10.1111/eos.12264
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of a new technique with pressure algometry applied to teeth in healthy Chinese individuals

Abstract: Pressure pain thresholds (PPTs) have been shown to be useful measures of mechanical pain sensitivity in deep tissues. However, clinical methods for measuring mechanical allodynia or hyperalgesia in teeth have not been reported. The aim of this study was to assess the reliability of PPTs in periodontal ligament of healthy Chinese participants. Twenty healthy young adults participated. Pressure pain thresholds were measured at six teeth and in two directions. The tests included three consecutive trials, in two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The inter-and intra-examiner reproducibility was not investigated in present study, however previous studies have shown a good inter-and intra-examiner reproducibility in terms of the thermal and mechanical QST in the orofacial regions [38,39].…”
Section: Somatosensory Abnormalities In Periodontitis Patients and Af...mentioning
confidence: 87%
“…The inter-and intra-examiner reproducibility was not investigated in present study, however previous studies have shown a good inter-and intra-examiner reproducibility in terms of the thermal and mechanical QST in the orofacial regions [38,39].…”
Section: Somatosensory Abnormalities In Periodontitis Patients and Af...mentioning
confidence: 87%
“… 47 The PPT can also be used to assess mechanical pain sensitivity in the periodontal ligament and gingiva. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical allodynia in the periodontal ligament around the canine tooth was investigated with the same method used in our previous study. 32 The force from the pressure algometer was applied directly to the crown of the canine tooth, and the recorded PPT may partially reflect the innervation patterns and receptor density in the periodontal ligament. 48 Interestingly, in the present study, significantly higher PPTs (i.e., decreased sensitivity) on the LLLT-treated side compared to the non-treated side were observed in the LG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A handheld pressure algometry (MEDOC, Israel) with a probe diameter of 0.8 cm was used to test pressure pain threshold (PPT). 11,19,20 The pressure was applied to the attached gingival tissues perpendicularly and crowns of the maxillary lateral incisors from two directions: one perpendicular to the center of facial surface of the crown labeled as "lateral"; the other direction was labeled as "vertical" when the pressure was applied parallel to the axis of the tooth. Three trials were made in random order at each tooth for the two sites and two different directions.…”
Section: Qstmentioning
confidence: 99%